The dual role of motivation on goals and well-being in higher vocational education students: a self-determination theory perspective - Wei Zhang; Kieran Balloo; Anesa Hosein; Emma Medland (Humanities & Social Sciences Communications)
Abstract Students’ well-being has received increasing international attention. However, research on well-being among higher vocational education (HVE) students, particularly in non-WEIRD contexts, remains limited. This study addresses this gap by investigating the relationships between goals, motivation, and well-being for HVE students in China through the lens of self-determination theory. A survey was administered to 1106 HVE students at a vocational college in China to collect data on their goal content, motivation, and well-being. Quantitative analyses revealed that motivation plays a dual role, acting as both a mediator and a moderator in the relationship between goals and well-being. This dual role is crucial for understanding not only how goals influence well-being but also under what conditions different types of goals promote or hinder well-being. Specifically, intrinsic goals, when paired with autonomous motivation, were found to significantly predict increased well-being. While extrinsic goals combined with controlled motivation also reliably predicted well-being, this relationship should be interpreted cautiously within the specific cultural context of the study. Furthermore, positive relationships between extrinsic goals and well-being, as well as between amotivation and well-being, were observed, contrasting findings from ‘WEIRD’ contexts. This study provides novel insights into how motivation functions as both a moderator and mediator in the goal-well-being relationship within a ‘non-WEIRD,’ specifically Chinese, HVE context. These findings underscore the importance of supporting students in pursuing goals to enhance their well-being. Further research is needed to explore these relationships in diverse cultural settings.